Latin versus European Power: A Tale of Two Market Reforms - Tim Mennel; Maria Fernanda Viecens (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper compares electricity market reforms in the European Union with reforms in Chile and Brazil. The paradigm of competitive market structures for the electricity sector, as developed in the economics literature, is outlined: competitive markets in generation and retailing and an independent regulator of the natural monopoly in transmission and generation. We present the institutional framework as well as the development of electricity markets in the European Union, Chile and Brazil and discuss in how far they comply with the textbook paradigm. Considerable differences emerge: While the European Union follows a path of full liberalization, facing, however, great difficulties in achieving unbundling of vertically integrated electricity companies and transnational competition, Chile and Brazil have only partially liberalized their electricity sector, enacting regulation to ensure household consumer protection and security of supply.
Keywords: 330; Elektrizitätswirtschaft; Deregulierung; Wirtschaftspolitische Wirkungsanalyse; Vergleich; Wettbewerb; EU-Staaten; Chile; Brasilien